Aeschynanthus chayangtajoensis (Gesneriaceae), a new species from Arunachal Pradesh, India - Chowlu, Krishna; Shenoy, Akshath; Ray, Ajit; Kabeer, Althaf Ahamed (Phytotaxa, 2024)
Aeschynanthus chayangtajoensis, a new species of Gesneriaceae from East Kameng district of Arunachal Pradesh, India, is described and illustrated. It is morphologically similar to A. acuminatus, A. moningerae and A. pedunculatus, in habit, shape and texture of leaves, inflorescence, and seeds with single hilar appendage, but differs from all by gibbous corolla base, completely glabrous gynoecium and much smaller fruit. A detailed description of the new species with color photographs and a comparison table of similar species are provided. The new species is evaluated and provisionally assessed as ‘Critically Endangered (CR)’ according to IUCN Red List Criteria.